Acute Water Supplementation Improved the Body Composition of Young Female Adults After Water Restriction of 12 h in Baoding, China: A Randomized Controlled Trial (RCT) - Zhang, Jianfen; Zhang, Na; Du, Songming; Liu, Shufang; Ma, Guansheng (Frontiers in Nutrition, 2022)
Insufficient intake of water may influence the balance of water in the human body. In this study, we explore the impacts of water supplementation on body composition indices among young adults after 12 h of water restriction, with the aim to determine the optimum volume of water for improving body water composition. A randomized controlled trial study was conducted among 64 young men and women in Baoding, China. After fasting overnight for 12 h, anthropometric measurements and urine and blood samples were collected as a baseline test at 8:00 a.m. of Day 2. Body composition was determined by measuring the ECW (extracellular water), ICW (intracellular water), and TBW (total body water) through bioelectrical impedance analysis (BIA). The participants were randomly divided into four groups, including water supplementation (WS) groups 1, 2, and 3, with 500, 200, and 100 mL of water, respectively, and a no water supplementation (NW) group. After 90 min, they were reassessed in a rehydration test (at 10:00 a.m. of Day 2). Repeated measurement ANOVA was used to assess the impact of water supplementation on body composition. Comparing the baseline and rehydration tests, interactions between time and volume were not significant among the men (all p > 0.05). Among women, a significant interaction was only found in ECW (p = 0.043), with TBW tending toward being significant (p = 0.055). Comparing the baseline and rehydration tests, the ECW in WS group 1, WS group 3, and the NW group all decreased (p = 0.028, p = 0.001, and p = 0.029), with reductions of 0.1, 0.3, and 0.2 kg, respectively; however, no significant decrease was observed in WS group 2 (p = 0.329). Furthermore, comparing the WS groups with the NW group in the rehydration test, the differences were not significant (p = 1.000, p = 1.000, and p = 0.288, respectively). Between men and women within groups, all of the body composition indices differed significantly, both at baseline and rehydration tests (all p < 0.05). Water supplementation led to changes in the distribution of the water content in young female adults in this study—but not men—after 12 h of water restriction, with no decrease in ECW. Finally, we found that 200 mL was the minimum volume capable of improving the water content distribution in participants in this study. Trial Registration [www.chictr.org.cn], identifier [ChiCTR-IOR-17011568].